Ideologi Film Garin Nugroho - Ahmad Toni (PANTUN, 2019)
This study is based on qualitative research with critical discourse analysis approach. The study presents the text of the fi lm as micro level of semiotic analysis. The purpose of the study is to uncover the ideology of Garin Nugroho fi lms which apply high aesthetic and anthropology construction of an exotic Indonesian culture. The result shows that the ideology resistance manifested in the fi lm of “Daun di Atas Bantal” is the philosophy reconstruction of art democratization as the power to suppress the regime of Suharto and the new order. “Opera jawa” fi lm is the reconstruction of gender philosophy and Java femininity as well as the philosophy of the nature cosmology in the perspective of moderate Hindu Islam in presenting the greediness of human in the system of the nature ecology. The fi lm of ‘Mata tertutup’ is the philosophy reconstruction of moderate Islam to counter the power of radicalism and terrorism as the concept developed and related to the tenacity of nationalism system of the young generation in Indonesia. “Soegija” fi lm is the reconstruction of Christology philosophy and the values of minority leadership in the nationhood and statehood. The fi lm of “Tjokroaminoto Guru Bangsa” is the reconstruction of Islam philosophy to view the humanism values in the establishment of the foundation of the nation as a moderate view.Keywords: film ideology, Garin Nugroho, Indonesian-ism